1985
DOI: 10.1007/bf00293024
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of unique DNA sequence heterozygosity in the human genome

Abstract: Fifteen different restriction fragment length polymorphisms (RFLPs) were detected in the human genome using 19 cloned DNA segments, derived from flow-sorted metaphase chromosomes or total genomic DNA, as hybridization probes. Since these clones were selected at random with respect to their coding potential, their analysis permitted an unbiased estimate of single-copy DNA sequence heterozygosity in the human genome. Since our estimate (h = 0.0037) is an order of magnitude higher than previous estimates derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(125 citation statements)
references
References 20 publications
4
121
0
Order By: Relevance
“…So, too, the response of individual patients to drug therapy is expected to be influenced by genomic variation, for example, because of differences in drug metabolism or the structure or function of drug receptor molecules. The most common type of DNA sequence variation, SNPs, are observed at a frequency of Ϸ1͞500-1,000 nucleotides in humans (31), and large-scale screening for SNPs (32) is now under way to advance efforts to identify disease susceptibility genes or to predict the response of individuals to drug therapies (33). Previous studies have indicated that a prolonged QT interval on a baseline electrocardiogram identifies individuals at increased risk for drug-induced arrhythmia, especially when administered medications that block cardiac potassium channels (9,11).…”
Section: Resultsmentioning
confidence: 99%
“…So, too, the response of individual patients to drug therapy is expected to be influenced by genomic variation, for example, because of differences in drug metabolism or the structure or function of drug receptor molecules. The most common type of DNA sequence variation, SNPs, are observed at a frequency of Ϸ1͞500-1,000 nucleotides in humans (31), and large-scale screening for SNPs (32) is now under way to advance efforts to identify disease susceptibility genes or to predict the response of individuals to drug therapies (33). Previous studies have indicated that a prolonged QT interval on a baseline electrocardiogram identifies individuals at increased risk for drug-induced arrhythmia, especially when administered medications that block cardiac potassium channels (9,11).…”
Section: Resultsmentioning
confidence: 99%
“…Three kinds of libraries have been used for cloning polymorphic DNA fragments: 1) a genomic library as we used in this report; 2) a genomic library prepared from a specific human chromosome or chromosome fragment, for instance a library from human-mouse hybrid cell DNA (Cavenee et al, 1984) or from DNA of flow sorted metaphase chromosomes (Cooper et al, 1985); 3) and a cDNA library of gene transcripts (Helentjaris and Gesteland, 1983). Using a library prepared from hybrid cell DNA or DNA of flow sorted metaphase chromosomes has the advantage of obtaining fragments from specific chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Single nucleotide polymorphisms (SNPs) are highly abundant sequence variations present within human populations that are estimated to occur on average one every 1000 base pairs. 34,35 Although the information content of each biallelic SNP marker is less than that of multiallelic microsatellite markers, this information can be rescued by examining moderately larger numbers of SNPs. A genetic map of 1500-3000 biallelic SNPs (with allele frequencies skewed as much as 80:20) should provide greater information content for traditional linkage studies relative to a current set of 300-400 microsatellite marker sets.…”
Section: Gene Mapping and Identificationmentioning
confidence: 99%